Response of Cuttings Material and Auxin Concentration to the Growth of Lemon Citrus Cuttings (Citrus limon L.) - Iskandar, Dede; Noertjahyani, Noertjahyani; Indriana, Kovertina Rakhmi (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
The experiment was carried out in Cikadu Village, Cijambe District, Subang Regency with an altitude of 250-400 above sea level and this experiment will be carried out from September to November 2022. The experimental design used is a factorial Randomized Group Design (RAK) with two treatment factors, namely factor cutting material (S) and Auxin concentration (A) and repeated 3 times. Based on the results of the analysis of observation data in the field, it can be concluded that the treatment of the cutting material has a significant effect on the age of germination, percentage of survival, number of shoots, number of leaves, number of roots and root volume. Treatment with a concentration of the auxin hormone at a concentration of 300 ppm (A4) affected the age of germination, percentage of life, number of shoots, number of leaves, number of roots and root volume